2005
DOI: 10.1016/j.bbi.2005.04.004
|View full text |Cite
|
Sign up to set email alerts
|

RU486 blocks the anti-inflammatory effects of exercise in a murine model of allergen-induced pulmonary inflammation

Abstract: In an ovalbumin (OVA)-driven murine model of allergic pulmonary inflammation, we have shown previously that moderate-intensity aerobic exercise training attenuates inflammatory responses, disease progression, and NF-κB activation within the sensitized lung. Glucocorticoids (GCs), potent anti-inflammatory agents, have been shown to alter transcriptional events that are important in asthmatic pathogenesis, such as NF-κB activation. Notably, exercise training can alter the production and signaling capacity of end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
45
1
6

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 46 publications
6
45
1
6
Order By: Relevance
“…These clinical benefits have also suggested a possible anti-inflammatory effect of aerobic training on asthma. Only few studies have investigated the anti-inflammatory effects of aerobic training on asthma, using an allergic murine model (40,41,61). In accordance with these studies, the anti-inflammatory effects of aerobic exercise could be attributed to decreased levels of IL-4, IL-5, IgE and also an increase in the antiinflammatory cytokine IL-10 (40,41,61).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…These clinical benefits have also suggested a possible anti-inflammatory effect of aerobic training on asthma. Only few studies have investigated the anti-inflammatory effects of aerobic training on asthma, using an allergic murine model (40,41,61). In accordance with these studies, the anti-inflammatory effects of aerobic exercise could be attributed to decreased levels of IL-4, IL-5, IgE and also an increase in the antiinflammatory cytokine IL-10 (40,41,61).…”
Section: Discussionmentioning
confidence: 63%
“…In previous studies, our and other groups have observed that low-and moderate-intensity aerobic exercise specifically decreases airway eosinophilic inflammation and remodeling (40,41,61). Recently, we demonstrated that low-and moderateintensity aerobic training decreases airway inflammation and remodeling in an experimental model of chronic allergic lung inflammation in mice and that these effects are not mediated by increased Th 1 response but could be partially mediated by increased interleukin (IL)-10 expression (61).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Shortly, these studies have demonstrated that these beneficial effects can be attributed to decreased activation of leukocytes and bronchial epithelial cells as a result of increased activation of glucocorticoids receptors, T-regulatory cells resulting in increased synthesis of anti-inflammatory cytokine IL-10, and decreased activation of transcriptional factor NF-kB [16][17][18][19][20][21][22][23][24]. In addition, these studies also demonstrated that aerobic exercise present a direct inhibitory effect on the pulmonary oxidants production as well as on the synthesis of mediators involved in the airway remodeling process [19,24].…”
mentioning
confidence: 99%
“…In this direction, since 2004 a growing number of experimental studies using mouse models of chronic allergic airway inflammation have demonstrated that low and moderate intensity aerobic exercise performed either before, during or after the allergen sensitization results in decreased eosinophilic inflammation, Th2 cytokines production, airway remodeling and hyperresponsiveness [16][17][18][19][20][21][22][23][24]. Shortly, these studies have demonstrated that these beneficial effects can be attributed to decreased activation of leukocytes and bronchial epithelial cells as a result of increased activation of glucocorticoids receptors, T-regulatory cells resulting in increased synthesis of anti-inflammatory cytokine IL-10, and decreased activation of transcriptional factor NF-kB [16][17][18][19][20][21][22][23][24].…”
mentioning
confidence: 99%